Hybrid Thermoelectrics: Molecular Level Insight into Enhanced n‐Type Transport in Solution‐Printed Hybrid Thermoelectrics (Adv. Energy Mater. 13/2019). Issue 13 (4th April 2019) - Zaia, Edmond W.; Gordon, Madeleine P.; Niemann, Valerie; Choi, Jaeyoo; Chatterjee, Ruchira; Hsu, Chih‐Hao; Yano, Junko; Russ, Boris; Sahu, Ayaskanta; Urban, Jeffrey J.
Abstract : In article number1803469, Jeffrey J. Urban and co‐workers demonstrate a novel n‐type hybrid organic‐inorganic thermoelectric material comprised of perylene diimide (PDI) small molecules and tellurium (Te) nanowires. Enhanced thermoelectric transport is observed in the composite, and detailed structural and energetic characterizations reveal that this increased performance is tied to a structural reorganization of the PDI molecules on the Te surface.